Microstructural and compositional evolution of core-shell FeSiAl composites during high-temperature annealing. Issue 17 (1st December 2019) - Liu, Dong; Gao, Shanmin; Zhang, Yue; Yu, Shengtao; Wang, Feng
Abstract: Core-shell structured magnetic composites containing a FeSiAl core and oxides shell were prepared by HNO3 oxidation. Microstructure evolution and phase composition of the insulation coatings correlated to magnetic properties have been revealed during high-temperature annealing. Results indicate that spherical nanoparticles composed of iron oxides may form on the coating surface after annealing at 700 °C followed by growing into larger wirelike particles by raising annealing temperature to 800 °C. The nucleation mechanism of the nanoparticles was presented according to the LaMer model and the growth regimes can be attributed to aggregative growth by mutual fusion. Largely enhanced magnetic properties ( μ e  = 167.3, P cv  = 205.6 mW/cm 3 ) have been achieved annealed at 750 °C.